2010
DOI: 10.1108/09578231011027824
|View full text |Cite
|
Sign up to set email alerts
|

Can ethics be learned?

Abstract: PurposeIn response to the growing need for educational leaders who possess ethical, critical and reflective qualities, a training program was developed based on ethics as a reflective critical capacity and on Starratt's three‐dimensional model. This paper aims to describe the impact of the program on ethical decision making and on educational leaders’ ethical competencies.Design/methodology/approachA three‐year action‐research study was conducted with three groups of educational administrators, totalling 30 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Meanwhile, other studies showed different results. These studies confirmed that taking educational courses of ethics changes the attitudes of people and motivate them to walk into moral paths (Glenn, 1992;Hiltebeitel & Jones, 1992;Eynon, Hill, & Stevens, 1997;Carlson & Burke, 1998;Shannon & Berl, 1997;Kerr & Smith, 1995;Trevino & McCabe, 1994;Owens, 1998;Hosmer, 1999;Langlois & Lapointe, 2010). Some studies also have suggested the positive impact of such courses on ethical decision making of people (Gautschi & Jones, 1998;Perri, Callanan, Rotenberry, & Oehlers, 2009).…”
Section: Theory and Hypothesesmentioning
confidence: 67%
See 1 more Smart Citation
“…Meanwhile, other studies showed different results. These studies confirmed that taking educational courses of ethics changes the attitudes of people and motivate them to walk into moral paths (Glenn, 1992;Hiltebeitel & Jones, 1992;Eynon, Hill, & Stevens, 1997;Carlson & Burke, 1998;Shannon & Berl, 1997;Kerr & Smith, 1995;Trevino & McCabe, 1994;Owens, 1998;Hosmer, 1999;Langlois & Lapointe, 2010). Some studies also have suggested the positive impact of such courses on ethical decision making of people (Gautschi & Jones, 1998;Perri, Callanan, Rotenberry, & Oehlers, 2009).…”
Section: Theory and Hypothesesmentioning
confidence: 67%
“…In their research, Abolmohammadi and Reeves (2000) examined the impacts of taking an ethics course during a semester on business ethics and social accountability of organization, and confirmed the positive impact of these courses. Results of a recent research by Langlois and Lapointe (2010) was conducted on three groups of managers and lasted for three years, and showed that the ethical behavior of managers changed after the study and such courses affected their ethical awareness, judgment, accountability and general behavior in business.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…While the ethic of critique addresses the presence of injustice in terms of human relations or organizational regulations within the organizational structure, the conduct of care strongly advocates the 'absolute respect' of interpersonal relations (Langlois et al, 2014). Their study results verified the presence and feasibility of the three ethical virtues in the process of moral dilemma resolutions (Langlois et al, 2014;Langlois & Lapointe, 2010). Since educational institutions become increasingly cognizant of the paramount importance of ethical leaders in the highly volatile and risky context of the Industrial Revolution 4.0, education administration must direct their attention to the ethical conducts of leadership (Langlois et al, 2014;Shapiro & Stefkovich, 2011;Starratt & Leeman, 2011).…”
Section: Langlois and Colleagues' Conceptualization Of Ethical Leadershipmentioning
confidence: 75%
“…The possession of value systems in conjunction with management skills and leadership practices enables educational leaders to 'account for a new kind of leadership-one based on moral authority' (Sergiovanni, 1992, p. 16). Ethical leadership lend credence to the significance of ethics in key educational and administrative decisions since ethical leaders primarily attribute better outcomes to the practice of ethical attitudes and behaviors (Langlois & Lapointe, 2010;Shapiro & Stefkovich, 2011;Starratt & Leeman, 2011;Van Niekerk et al, 2017).…”
Section: Langlois and Colleagues' Conceptualization Of Ethical Leadershipmentioning
confidence: 99%
“…Further, Langlois and Claire (2010) recognized that increasing the ethics of an individual is signi icant in becoming an effective leader. School administrators believed that possessing ethical and moral skills is important in coping with the complexities of the job (Ngang et al, 2015).…”
Section: Teamworkmentioning
confidence: 99%